Book review: Bogdan Murgescu, The Romanian Countries between the Ottoman Empire and Christian Europe - GHIORGHIŢĂ, Eugen (Annals of Spiru Haret University. Economic Series, 2014)
The works of Professor Bogdan Murgescu cover more than five centuries of economic, political and cultural history, of a wide geographical area, from the Atlantic to the Eastern borders of the former Ottoman Empire. .....